Trade flows, barriers and market drivers in renewable energy supply goods : the need to level the playing field - Jha, Veena (2009)
Focuses on trade flows and barriers to commercially available renewable energy generation technologies and their associated goods. Identifies and examines the role of various market and trade drivers including tariffs in the uptake of these technologies.